COPD treatment case I: COPD with “bronchitis attacks” - Kocks, Janwillem (Henry Stewart Talks, 2016)
The clinical COPD questionnaire (CCQ) score, Goals of COPD therapy, GOLD guideline, Case management, An updated version, which will include the latest GOLD COPD recommendations, will be released in November 2017